Preferensi Konsumen Terhadap Kopi Kemasan Siap Minum di Kecamatan Tambun Selatan, Kabupaten Bekasi - Putri, Tajwina Ulya; Trimo, Lucyana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
In this modern era that demands everything to be fast and convenient, Ready-to-Drink Packaged Coffee emerges to support the modern lifestyle where convenience influences people's purchasing decisions. When consuming a product, consumers will choose products according to their preferences to maximize individual satisfaction, thus requiring consumer preference research. The aim of this research is to identify consumer characteristics, understand consumer preferences regarding taste attributes, flavor variants, price, packaging, and volume, as well as to determine the attribute sequence of the product based on its importance to consumers of ready-to-drink packaged coffee in Tambun Selatan Sub-District, Bekasi Regency. The research design used in this study is quantitative descriptive with survey techniques using questionnaires. There are 120 respondents in total which are residents of Tambun Selatan Sub-District aged 15 and above who have purchased and consumed ready-to-drink packaged coffee. The data analysis techniques used are Chi-square test and Fishbein multi-attribute analysis. The research findings reveal that the preferred ready-to-drink packaged coffee among consumers in Tambun Selatan Sub-District is creamy flavor, caffe latte flavor variant (milk coffee), priced between Rp 3,000 – Rp 8,500, packaged in plastic bottles, and medium-sized, ranging from 200 ml – 250 ml. The sequence of attribute importance for ready-to-drink packaged coffee according to consumers is taste, price, volume, flavor variants, and packaging.